Widespread coastal upwelling along the Eastern Paleo-Tethys Margin (South China) during the Middle Permian (Guadalupian): Implications for organic matter accumulation. (November 2018) - Zhang, Bolin; Yao, Suping; Wignall, Paul B.; Hu, Wenxuan; Ding, Hai; Liu, Biao; Ren, Yongle
Abstract: Guadalupian organic-rich depositions within the eastern Paleo-Tethys Margin have been attributed to coastal upwelling, but the idea has not been tested. Here, a suite of geochemical proxies from the Gufeng Formation of the Lower Yangtze region (South China) are used to investigate the formation mechanisms of organic matter accumulation. A high organic carbon content and similar enrichments of bio/redox-sensitive trace metals show strong similarities to the geochemical characteristics of modern upwelling sediments. The use of high Cd/Mo ratios and low Co x Mn values characteristic of modern upwelling settings (Sweere et al., 2016) is replicated in the Gufeng strata implying that Lower Yangtze area was dominated by persistent upwelling that become less intense (seasonal?) later in the Guadalupian. Application of these new geochemical proxies shows that the characteristics of modern upwelling systems, such as the formation of an intense oxygen minimum zone (OMZ), can be confirmed in the ancient. Calculation estimates show that primary productivity was sustained at moderate to high levels and was at comparable levels to those of the modern Peru upwelling system. OMZ-related anoxic conditions (with transient euxinic episodes) dominated permanently during the deposition of the Gufeng Formation and then became more intense conditions (euxinia) later in the Guadalupian. The radiolarian chert/siliceous mudstone rhythms that coincide with fluctuations in major elements, organic carbon, total sulfur and trace metal concentrations may reflect dilution by biogenic silica. Chert Zr/Al ratios are also higher than in mudstone suggesting the cherts may record more winnowed deposition at the margin of an ancient OMZ compared with a location within the OMZ for the mudstone. The organic matter accumulation of the Middle Permian Gufeng Formation may be mainly controlled by the upwelling-driven primary productivity and also influenced by the changes of anoxic/euxinic conditions and the dilution of biogenic silica. Highlights: An ancient coastal upwelling with high productivity and intense OMZ dominated along the eastern Paleo-Tethys Margin. Both high Cd/Mo ratios and low Co x Mn values provide a powerful tool for distinguishing ancient upwelling environments. The primary productivity plays a major role in organic matter accumulation.